Legal Principles of the Process of Transferring Land Rights Using a Notarial Deed - Fitri Wahyuni; Efik Yusdiansyah; Riny Irianti Sundary (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
A notarial deed, particularly the Sale and Purchase Binding Agreement (PPJB), remains a controversial instrument in the process of transferring land ownership rights. This phenomenon is commonly found in society, where many laypeople assume that a PPJB is sufficient to process the transfer of title (balik nama) of purchased land. In practice, however, issues may arise when the PPJB, especially those executed before a Notary, does not clearly stipulate the rights and obligations of the parties involved. This condition may lead to disputes, considering that the PPJB serves as a preliminary agreement and a reference for the Deed of Sale and Purchase (AJB) prepared by the Land Deed Official (PPAT), which is a formal requirement for the legal transfer of land rights. This research employs a descriptive-analytical approach using a normative legal method based on literature review. The objective of this study is to examine and demonstrate the legal principles concerning binding force and legal protection for parties engaged in a notarial PPJB, as part of the broader philosophy of legal order within the state.